Perceived biodiversity: Is what we measure also what we see and hear? - Kevin Rozario; Taylor Shaw; Melissa Marselle; Rachel Rui Ying Oh; Erich Schröger; Mateo Giraldo Botero; Julian Frey; Valentin Ștefan; Sandra Müller; Michael Scherer‐Lorenzen; Bogdan Jaroszewicz; Kris Verheyen; et al. (People and Nature)
Abstract Biodiversity is crucial for human health and well‐being. Perceived biodiversity—people's subjective experience of biodiversity—seems to be particularly relevant for mental well‐being. Using photographs and audio recordings of forests that varied in levels of biodiversity, we conducted two sorting studies to assess how people perceive visual and acoustic diversity and whether their perceptions align with species richness and proxies for forest structural diversity (‘actual diversity’). Per study, 48 participants were asked to sort the stimuli according to any similarity‐based sorting criteria they liked (‘open sorts’) and perceived diversity (‘closed sorts’). The main perceived visual forest characteristics identified by participants in the open visual sorts were vegetation density, light conditions, forest structural attributes and colours. The main perceived acoustic forest characteristics identified in the open acoustic sorts comprised bird song characteristics, physical properties such as volume, references to the time of day or seasonality and evoked emotions. Perceived visual and acoustic diversity were significantly correlated with actual visual and acoustic diversity, respectively. We further computed several objective visual and acoustic diversity indices from the photos and audio recordings, for example, a Greenness Index or the Acoustic Complexity Index, and assessed their relevance for perceived and actual diversity. While all acoustic diversity indices were significantly associated with perceived and actual acoustic diversity, for the visual sense, the Greenness Index successfully captured both perceived and actual visual diversity. Our results suggest that people can perceive variations in biodiversity levels. Our identified visual and acoustic forest characteristics may help to better understand perceived diversity and how it differs from how diversity is measured in biological studies. We present one visual and several acoustic diversity indices that quantify aspects of perceived and actual diversity. These indices may serve as cost‐efficient tools to manage and plan greenspaces to promote biodiversity and mental well‐being. Read the free Plain Language Summary for this article on the Journal blog.